Three‐dimensional analysis of carbon nanotube‐reinforced cylindrical shells with temperature‐dependent properties under thermal environment. Issue 4 (29th April 2016) - Pourasghar, A.; Moradi‐Dastjerdi, R.; Yas, M.H.; Ghorbanpour Arani, A.; Kamarian, S.
Abstract : In this article, the three‐dimensional thermo‐elastic deformation of cylindrical shells reinforced by single‐walled carbon nanotubes (SWCNTs), subjected to thermal load is analyzed. The cylindrical shell has been reinforced by Carbon Nanotube (CNT) in the radial direction and the material properties are estimated by the extended rule of mixture. The material properties are temperature dependent and suitable temperature and displacement functions that identically satisfy boundary conditions at the edges are used to reduce the equilibrium equations to a set of coupled ordinary differential equations (ODE) with variable coefficients, which are solved by Generalized Differential Quadrature (GDQ) method. Accuracy of the presents approach is validated by comparing the numerical results with the available published results in the literature. POLYM. COMPOS., 39:1161–1171, 2018. © 2016 Society of Plastics Engineers